2015
DOI: 10.3945/jn.115.213439
|View full text |Cite
|
Sign up to set email alerts
|

Iodine Supplementation Decreases Hypercholesterolemia in Iodine-Deficient, Overweight Women: A Randomized Controlled Trial ,

Abstract: Our findings suggest that moderate to severe iodine deficiency in overweight women elevates serum TSH and produces a more atherogenic lipid profile and that iodine supplementation in this group reduces the prevalence of hypercholesterolemia. Thus, iodine prophylaxis may reduce cardiovascular disease risk in overweight adults. This trial was registered at clinicaltrials.gov as NCT01985204.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 33 publications
2
20
0
Order By: Relevance
“…Iodine supplement treatment for euthyroid goiter on children resulted significant decrease in total cholesterol and LDL cholesterol to their normal level [ 43 ]. A recent randomized controlled intervention study also reported that 6-month intervention with iodine supplementation significantly decreased risks for hypercholesterolemia in overweight and obese Moroccan women [ 44 ]. Additionally, a rural African population-based study reported that pregnant women and their offspring in an iodine deficient area are more likely to have a risk of coronary complications and hyperlipidemia compared to non-iodine deficient region [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Iodine supplement treatment for euthyroid goiter on children resulted significant decrease in total cholesterol and LDL cholesterol to their normal level [ 43 ]. A recent randomized controlled intervention study also reported that 6-month intervention with iodine supplementation significantly decreased risks for hypercholesterolemia in overweight and obese Moroccan women [ 44 ]. Additionally, a rural African population-based study reported that pregnant women and their offspring in an iodine deficient area are more likely to have a risk of coronary complications and hyperlipidemia compared to non-iodine deficient region [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moderate iodine diets improve the lipid profile in mice, increasing low density lipoprotein receptors and scavenger receptor class B type 1 (SR-B1) in liver [46]. Moreover, iodine supplementation decreased hypercholesterolemia in overweight women [47]. More recently, our group showed that a moderate I 2 supplement prevented the pancreatic damage secondary to hypothyroidism by methimazole, normalizing thyroid hormone synthesis in the thyroid and preventing the oxidative status in pancreatic tissue [48].…”
Section: Antioxidant Effectsmentioning
confidence: 97%
“…These findings suggest that moderate to severe iodine deficiency in overweight women elevates serum TSH and produces a more atherogenic lipid profile and iodine prophylaxis can reduce disease risk in overweight adult [39].…”
Section: Strong Evidence On Iodine Intakementioning
confidence: 81%